THE DEVELOPMENT ESP WEB BASED LEARNING MATERIAL FOR NURSING STUDENTS OF INSTITUT TEKNOLOGI KESEHATAN (ITEKES) BALI - Suryati, Ni Wayan Novi; Susanta, I Putu Agus Endra; Dewi, Kadek Maya Cyntia (International Conference on Cultural Studies, 2019)
English is one of the compulsory subjects taught in Nursing Study Program in Institut Teknologi Kesehatan (ITEKES) Bali. During the English learning, there are 2 major problems faced by both the lecturers and the students; English learning material which still presents general English and the learning process that has not utilized technology yet. This research aimed at (1) identifying the nursing students’ needs toward English learning material, (2) analyzing the appropriate web-based English learning material for nursing students, and (3) designing and developing the suitable web-based English learning material for nursing students of ITEKES Bali. This was a research and development following 3 stages, namely (1) analyzing the needs through questionnaires, (2) developing a prototype and trying out, (3) validating the product. Thirty nursing students and 10 nurses were involved in this study. It was found that they need an English learning material covering the language expression of greeting and welcoming patients, establishing a relationship with patients, human body, respiratory system, digest system, neuron system, immune system, cardiovascular system, reproduction system, and family care. Based on the results of expert validation, the developed English material can be implemented in an English learning for nursing students.